HPLC METHOD FOR QUANTIFICATION OF ELLAGIC ACID IN IN VIVO AND IN VITRO PLANT PARTS OF OROXYLUM INDICUM (L.) VENT. - Rami, Esha; Rami, Saurabh; Patel, Illa (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The present study was performed to investigate the comparative analysis of ellagic acid content in in vivo (stem, leaf and root) and in vitro (callus, in vitro developed root and shoot) samples of Oroxylum indicum (L.) Vent. an important medicinal plant. Methods: For in vitro culture, seedling explants were inoculated on MS (Murashige and Skoog's, 1962) medium, supplemented with BAP and Kn alone and combination with IAA. Analytical method HPLC was developed for the quantification of ellagic acid in in vivo and in vitro samples. Result: BAP combination with IAA was best for shoot multiplication, BAP with 2,4-D were used for callus proliferation. HPLC analysis of these extracts revealed that the quantity of ellagic acid present in both the samples but maximum ellagic acid content was obtained in leaves among all plant parts. Conclusion: Hence, the present study showed the in vivo as well as in vitro samples contain ellagic acid. That can be used for its large scale production in future. Key-words: Oroxylum indicum, ellagic acid, HPLC